Application of plant extracts cosmetics in the field of anti-aging - Minghui Xie; Zibing Jiang; Xingyue Lin; Xingchuan Wei (Journal of Dermatologic Science and Cosmetic Technology, 2024)
Skin aging is a direct manifestation of body aging, representing a complex and irreversible natural process, which is influenced by genetics, lifestyle and environmental factors. In the process of skin aging, the skin epidermis gradually become thinner, the inherent repair ability gradually weakens, the collagen and elastin gradually decrease and the skin gradually loses elasticity. Although skin aging is inevitable, it can be delayed to some extent by using cosmetics. Natural extract cosmetics are highly favored by consumers for their safety and efficacy, aligning with consumer preferences for natural, organic, efficient and sustainable skincare concepts. Numerous plant resources in nature possess superior properties like moisturizing, barrier repair, anti-oxidation, sunscreen whitening and anti-inflammatory properties after thousands of years of natural selection. These properties enable plant components to effectively enhance the anti-aging effects of skincare products through multiple anti-aging pathways, which can be widely used to develop natural anti-aging skin care products.